APPLICATION OF PROJECT-BASED LEARNING IN IMPROVING UNDERSTANDING OF LOGISTICS MANAGEMENT IN SIKECE PURWAKARTA MACARONI MSMES - Dhandi Apriandi; M. Rifan Nawawi; Rifki Hidayat; Wina Novianti (Journal Tourism Nomic, 2026)
This study aims to analyze the implementation of logistics management practices in Makaroni SiKece, a micro, small, and medium enterprise (MSME) located in Purwakarta Regency. After the COVID-19 pandemic, the enterprise experienced a decline in production and distribution capacity due to inefficient logistics management, including raw material procurement, storage, inventory recording, and product delivery. Most logistics activities were still carried out manually and centralized by the business owner, which caused delays in distribution and limited market expansion. This research employed a qualitative descriptive approach to explore existing logistics practices and identify improvement opportunities. Data were collected through observation, interviews with the business owner, and documentation of operational activities. The analysis focused on key logistics components such as inventory management, distribution route planning, packaging standardization, and the use of simple digital tools for stock recording and distribution mapping. The findings reveal that limited knowledge of logistics management and the absence of structured procedures significantly affect operational efficiency. However, the adoption of basic logistics management concepts and simple digital tools can support better inventory control and distribution planning. The study concludes that improving logistics management practices is essential to enhance operational efficiency and strengthen the competitiveness of MSMEs in local markets.